Social protection innovative practice responses to COVID-19 at local level in Serbia - Matkovic, Gordana (Ревија за социјална политика/Journal of Social Policy, 2021)
This article presents social protection innovative practices at the local level during the state of emergency due to the COVID-19 pandemic in Serbia from March 15 until May 6, 2020. Forty collected innovative practices and in-depth interviews provide an overview of local responses to crisis in selected municipalities and cities. Local governments established crisis headquarters and call centres, introduced shift work and work from home in local institutions and engaged a number of volunteers. Call centres received citizens’ requests, provided information and even basic psychosocial support. Procedures were simplified, and applications were accepted by phone, mail, and e-mail for both services and material support. Rapid vertical and horizontal expansion of financial assistance and home care programs was an important goal in some communities. Community based service staff established communication with beneficiaries via digital devices, but also in backyards and at doorsteps. Soup kitchen programs were adopted to crisis circumstances, by delivering meals at home and/or delivery of foodstuff and dry instead of cooked meals. Issuing lockdown movement permits and providing different kind of assistance to the elderly were the main additional crisis related focus. Some local governments have made a special effort to identify vulnerable, to improve homeless care and to support Roma settlements. The article presents in more detail a number of individual examples of innovative practice.
Keywords: innovative practice; local level; COVID-19; community-based services; material support